Exploring 10–15-year-old patients' perspectives of fixed orthodontic treatment. (June 2021) - Longstaff, Sarah; Davies, Katherine; Benson, Philip
Objective: To explore and understand young people's perspectives of fixed orthodontic treatment. In particular, understanding how young people perceived and experienced having a fixed appliance and how their experiences can change during their treatment. Design: Qualitative study carried out longitudinally. Setting: In-depth qualitative interviews carried out in participants' homes, video diaries recorded by participants when and where they wish. Participants: Fifteen patients aged 10–15 years undergoing NHS fixed appliance treatment. Methods: Data were collected by in-depth interviews and video diaries throughout the participants' course of orthodontic treatment. Data were analysed using thematic analysis. Results: Young people's friends, family and social media influenced how young people felt about the appearance of their teeth. Young people can perceive negative social judgements are made about them based on the appearance of their teeth; however, the appearance of the brace was not a concern. For some of the young people, the presence of the brace formed a rite of passage throughout adolescence. Pain and discomfort caused by fixed appliances was expected and tolerated and felt normal with time. Conclusion: Young people's perceptions about appearance are influenced by people around them and social media. The physical feeling of the brace was normalised, although it did affect young people's lives.